Potensi Ekstrak Etanol Ubi Jalar Ungu sebagai Inhibitor Angiotensin Converting Enzyme pada Tikus Hipertensi - Rahmawati, Irma Sarita; Soetjipto, Soetjipto; Catur Adi, Annis; Aulanni’am, Aulanni’am; Rizky Maulidiana, Annisa (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2021)
There is an increasing amount of evidence that oxidative stress related to hypertension can damage the function of diverse structures such as the aorta and kidney. It is a well-established fact that chlorogenic acid and anthocyanin found in purple sweet potato generates bioactive compound with antihypertensive and anti-ACE activities in RAA system. The present study sought to investigate anti-ACE activities in RAA system of extract ethanol of purple sweet potato (EP) in deoxycorticosterone acetate (DOCA–salt)–induced hypertensive rats (Rattus norvegicus). The rats were orally administrated a 95% ethanol extract of purple sweet potato (var. ayamurasaki) (EP) in a daily dose of 200 and 400 mg/kg body weight also chlorogenic acid (CA) of 700 mg/kg bw for 4 weeks. Activity of renin, ACE, and Ang II concentration were assessed. Inhibiting activity of renin, ACE, and decreasing Ang II concentration after treatment was observed in the DOCA-salt hypertensive rats compared to normotensive group rats; (P<0.05). This is the first report that demonstrates the lowering of blood pressure and anti-ACE in RAA-system effects of an ethanol extract of purple sweet potato, containing chlorogenic acid, in a DOCA–salt model of hypertension.